An Analysis of Languages on Instagram @Erina_S_Gudono (Semantic Study) - Anggelina Nahak (RETORIKA: Jurnal Ilmu Bahasa, 2024)
This study aims to analyze the linguistic style used in the comment section of the Instagram account @Erina_S_Gudono using a semantic approach. The focus of the research is on the meanings of words, phrases, and linguistic signs used in netizens' comments, particularly in the sarcasm language. This research employs a qualitative method, where data is collected from comments left by netizens on posts from this account during the period of August 2024. The findings indicate that sarcasm is the dominant linguistic style, with the use of the word malu (shame) frequently appearing in the context of criticism toward actions or sarcastic phrases on the @Erina_S_Gudono account. Netizens use sarcasm as a way to express disappointment or dissatisfaction, employing words that contain sharp insinuations and social critique. The main conclusion of this research is that sarcasm in Instagram comments often serves as a tool to convey criticism in an indirect yet emotionally charged manner, which has the potential to create an aggressive online communication environment. This study provides insights into the dynamics of language use on social media and how semantics plays a role in uncovering the hidden meanings of language interactions on digital platforms.